Optimizing Plant Spacing to Improve Growth and Yield of Sweet Potato (Ipomoea batatas L.) Under Low Soil Fertility Conditions - Muzna Ardin Abdul Gafur; Zulkarnain Sangadji; Desi Ratna Sari (Jurnal AGRO, 2026)
Sweet potato (Ipomoea batatas L.) is an important food crop in tropical regions, but its productivity remains low on infertile soils where suboptimal agronomic practices, including inappropriate plant spacing, restrict plant growth and tuber development. This study evaluated the effect of different plant spacing arrangements on the growth and yield of sweet potato cultivated under low soil fertility conditions. A randomized complete block design with six spacing treatments J1 (40 × 30 cm), J2 (50 × 50 cm), J3 (75 × 30 cm), and J4 (75 × 50 cm) and three replications was used. Growth parameters and yield components were analyzed using analysis of variance followed by the Honest Significant Difference (HSD) test at the 5% significance level. Plant spacing significantly affected vegetative growth and tuber yield. The spacing of 75 × 50 cm produced the best overall performance, resulting in the highest plant height (278.83 cm), the greatest number of leaves (33.28 leaves plant⁻¹), the largest tuber diameter (5.49 cm), the highest tuber weight per plant (2.83 oz plant⁻¹), and the highest tuber weight per plot (4.53 kg plot⁻¹), equivalent to an estimated yield of 12.58 t ha⁻¹. The superior performance of this spacing is attributed to a more favorable balance between plant population and competition for light, water, and nutrients, thereby enhancing photosynthetic efficiency and assimilate partitioning to storage roots. These findings demonstrate that optimizing plant spacing is an effective and practical agronomic strategy for improving sweet potato productivity on low-fertility soils and may contribute to more sustainable sweet potato production in similar agroecological environments. Keywords: sweet potato, plant spacing, low-fertility soil, tuber yield, agronomic management.   ABSTRAK Ubi jalar (Ipomoea batatas L.) merupakan tanaman pangan penting di wilayah tropis, namun produktivitasnya masih rendah pada tanah kurang subur akibat praktik agronomi yang suboptimal seperti pengaturan jarak tanam yang tidak tepat yang menghambat pertumbuhan tanaman dan perkembangan umbi. Penelitian ini mengevaluasi pengaruh berbagai pengaturan jarak tanam terhadap pertumbuhan dan hasil ubi jalar yang dibudidayakan pada kondisi tanah dengan tingkat kesuburan rendah. Penelitian menggunakan rancangan acak kelompok lengkap dengan enam perlakuan jarak tanam J1 (40 × 30 cm), J2 (50 × 50 cm), J3 (75 × 30 cm), dan J4 (75 × 50 cm) serta tiga ulangan. Parameter pertumbuhan dan komponen hasil dianalisis menggunakan analisis ragam yang diikuti dengan uji Beda Nyata Jujur (BNJ) pada taraf signifikansi 5%. Jarak tanam berpengaruh nyata terhadap pertumbuhan vegetatif dan hasil umbi. Jarak tanam 75 × 50 cm menghasilkan performa terbaik secara keseluruhan, dengan capaian berupa tinggi tanaman tertinggi (278,83 cm), jumlah daun terbanyak (33,28 helai tanaman⁻¹), diameter umbi terbesar (5,49 cm), bobot umbi per tanaman tertinggi (2,83 oz tanaman⁻¹), dan bobot umbi per petak tertinggi (4,53 kg petak⁻¹), yang setara dengan estimasi hasil 12,58 ton ha⁻¹. Performa unggul pada jarak tanam ini disebabkan oleh keseimbangan yang lebih baik antara populasi tanaman dan kompetisi untuk mendapatkan cahaya, air, dan hara, sehingga meningkatkan efisiensi fotosintesis serta alokasi asimilat ke akar penyimpanan (umbi). Temuan ini menunjukkan bahwa optimalisasi jarak tanam merupakan strategi agronomi yang efektif dan praktis untuk meningkatkan produktivitas ubi jalar pada tanah kurang subur, serta dapat berkontribusi pada produksi ubi jalar yang lebih berkelanjutan di lingkungan agroekologi serupa. Kata kunci: ubi jalar, jarak tanam, tanah kurang subur, hasil umbi, pengelolaan agronomi.